Are we apathetic? surveying Singaporeans' political attitudes, participation, and knowledge. - Chan, Boon Wee. (2008)
A representative nationwide survey using CATI was conducted in Singapore with adults aged 18 years above. Findings showed Singaporeans' mean level of trust in the government was fairly high, while the mean level of political knowledge was average. However, political participation, internal efficacy, external efficacy and political interest all had low means.